Understanding GenAI Adoption in Education: A Systematic Literature Review - Hidayat, Alifiansyah Arrizqy; Rospricilia, Tita Ayu; Rosidah, Nur Azizah; Fauzia, Ramadhani Vanva; Putra, Ian Mahendra (Journal of Multimedia Trend and Technology, 2025)
This study conducts a systematic literature review of 40 peer-reviewed articles to investigate behavioral factors influencing the adoption of Generative Artificial Intelligence (GenAI) in education. Using PRISMA guidelines, the review identifies key constructs from the Unified Theory of Acceptance and Use of Technology (UTAUT) including performance expectancy, effort expectancy, social influence, and facilitating conditions as consistent predictors of GenAI usage. Additionally, complementary variables such as trust, perceived risk, self-efficacy, hedonic motivation, and ethical concerns are found to significantly shape user engagement. The integration of UTAUT with models like TAM, TPB, and SCT enhances explanatory depth, offering a multidimensional framework for understanding GenAI adoption. The study proposes a conceptual model and highlights the importance of inclusive, context-sensitive approaches to support responsible GenAI integration in academic settings.